2020
DOI: 10.3390/ijms21103610
|View full text |Cite
|
Sign up to set email alerts
|

Mir-370-3p Impairs Glioblastoma Stem-Like Cell Malignancy Regulating a Complex Interplay between HMGA2/HIF1A and the Oncogenic Long Non-Coding RNA (lncRNA) NEAT1

Abstract: Glioblastoma (GBM) is the most aggressive and prevalent form of a human brain tumor in adults. Several data have demonstrated the implication of microRNAs (miRNAs) in tumorigenicity of GBM stem-like cells (GSCs). The regulatory functions of miRNAs in GSCs have emerged as potential therapeutic candidates for glioma treatment. The current study aimed at investigating the function of miR-370-3p in glioma progression, as aberrant expression of miR-370-3p, is involved in various human cancers, including glioma. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…Anchorage-dependent cell lines T98G, U-251 MG and U-87 MG were cultured as previously reported (21). Anchorageindependent TS#1, TS#83 and TS#163 neurospheres are patient-derived cell lines from surgical samples classified according to WHO 2016 (22), isolated and cultured in order to enrich them with glioma stem cells, as described (19,23,24). Human hTERT-immortalized retinal pigment epithelial cells (RPE-1) (20) were a kind gift from Giulia Guarguaglini, CNR, Rome, Italy.…”
Section: Cell Linesmentioning
confidence: 99%
“…Anchorage-dependent cell lines T98G, U-251 MG and U-87 MG were cultured as previously reported (21). Anchorageindependent TS#1, TS#83 and TS#163 neurospheres are patient-derived cell lines from surgical samples classified according to WHO 2016 (22), isolated and cultured in order to enrich them with glioma stem cells, as described (19,23,24). Human hTERT-immortalized retinal pigment epithelial cells (RPE-1) (20) were a kind gift from Giulia Guarguaglini, CNR, Rome, Italy.…”
Section: Cell Linesmentioning
confidence: 99%
“…Comparison of transcriptomes of GBM cells treated with HMGB1 and PBS showed that the expression of NEAT1, a lncRNA reportedly playing important roles in GSCs (Gong et al, 2016;Yang et al, 2017;Lulli et al, 2020), was significantly upregulated (Figure 7A). qRT-PCR confirmed the proportional upregulation of NEAT1 in the presence of increasing concentrations of HMGB1 (Figure 7B).…”
Section: Lncrna Neat1 Is Required For the Formation Of Hmgb1 Induced mentioning
confidence: 99%
“…Regarding brainstem CCMs, miR-370-3p might also present biological or pathophysiological importance for patients harboring lesions at this level by targeting the gene Neurofibromatosis type 1 [119]. Lulli et al have shown that miR-370-3p expression is markedly downregulated in gliomas when compared to normal brain tissue and neural stem cells [153]. The recovery of miR-370-3p expression in glioblastoma stem-like cells considerably reduced their proliferation, migration, and clonogenic abilities both in vitro, and in vivo models.…”
Section: Mir-370-3pmentioning
confidence: 99%